CONSERVATIVE TECHNIQUE OF PLACENTA ACCRETA SPECTRUM DISORDER (PASD) - A. F. S., DESYHANDAYANI; LUBIS, MUARA P. (International Journal of Current Pharmaceutical Research, 2020)
This article review was aimed to discuss about the choices of conservative technique of placenta accrete spectrum disorder. Placenta Accreta Spectrum Disorder (PASD) is an obstetric complication complexes which tend to cause high maternal morbidity. Maternal morbidity has been reported in 60% of cases and mortality reaches 7% in women with placenta accreta. Internationally, the incidence of abnormal placental invasion has increased in the last 30 y and is currently reported to occur in 2–90 per 10,000 deliveries. Main cause of PASD is uterine surgery in particular, scars from cesarean section, a 56-fold increase in risk after three times cesarean section. In cases without massive bleeding and coagulopathy, a conservative approach can be considere. Four main conservative management methods have been described in several international literature, namely extirpative techniques (manual removal of the placenta); leaving the placenta in situ or an observative approach; one-step conservative operation (removal of the location of the accreta; and Triple-P procedure (stitching around the accretion area after resection).